2017
DOI: 10.21825/vdt.v86i4.16187
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanische aspecten met betrekking tot hoefbeslag bij paarden

Abstract: In dit artikel wordt een overzicht gegeven van de huidige biomechanische inzichten die nuttige aanwijzingen kunnen verschaffen voor “evidence-based” keuzes omtrent het bekappen en/of het aanbrengen van hoefbeslag in de behandeling van kreupelheid bij het paard. De nadruk wordt gelegd op een optimale hoefbalans, de absorptie van schokken, de gepaste mate van grip/afremmen versus glijden, optimale drukverdeling binnen de hoef, en het bevorderen van “breakover”. Ook met het hoefmechanisme moet rekening gehouden w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…There is potential for improvement regarding the recommendations for therapeutic trimming and shoeing, especially in cases of DDFT pathology; egg-bar shoes or other forms of palmar/plantar support, in combination with optimized break-over, may be bene-ficial for these cases as recently reviewed by Oosterlinck et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…There is potential for improvement regarding the recommendations for therapeutic trimming and shoeing, especially in cases of DDFT pathology; egg-bar shoes or other forms of palmar/plantar support, in combination with optimized break-over, may be bene-ficial for these cases as recently reviewed by Oosterlinck et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Pitti et al [24] studied the peak vertical GRF and VI of normal pony and unilateral limping pony with forelimb and found that there was a significant difference between healthy pony and limping pony. Oosterlinck et al [25] studied the balance between the left and right hoofs, the front and hind hoofs, and the pressure distribution of the hoof bottom with the limp horse as the test object. Panagiotopoulou et al [26] selected seven discrete regions of interest on the plantar pressure contours of adult African elephants and Asian elephants and analyzed their foot pressure distribution patterns and COP trajectories.…”
Section: Introductionmentioning
confidence: 99%